2017
DOI: 10.1002/2017jg004010
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions Under Different Drainage and Flooding Regimes of Cultivated Peatlands

Abstract: Globally, approximately 10–20% of peatlands have been drained for agricultural purposes. A strategy to protect peatlands and mitigate carbon dioxide (CO2) emissions, while continuing agricultural production, is the use of intermittent flooding and drainage. A potential drawback of this strategy could be increases in methane (CH4) and nitrous oxide (N2O) emissions. The objective of this study was to compare greenhouse gas (GHG) emissions from peatlands under various flooding–drainage cycles. A laboratory study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 81 publications
(122 reference statements)
3
25
1
Order By: Relevance
“…The estimated CO 2 annual emissions from EAA soils exposed to constantly drained conditions in this study (298 g CO 2 –C m −2 yr −1 ) are similar to previous estimates of oxidation from drained EAA peats obtained using soil cores in a laboratory setting (219 g CO 2 –C m −2 yr −1 ) (Hu et al., 2017) and to the estimates of soil cores from Everglades mangrove peats (∼278 g CO 2 –C m −2 yr −1 ) (Chambers et al., 2014). In our study, vegetation was excluded with the intention of estimating oxidation only from the decomposition of the organic matter present in the soil.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The estimated CO 2 annual emissions from EAA soils exposed to constantly drained conditions in this study (298 g CO 2 –C m −2 yr −1 ) are similar to previous estimates of oxidation from drained EAA peats obtained using soil cores in a laboratory setting (219 g CO 2 –C m −2 yr −1 ) (Hu et al., 2017) and to the estimates of soil cores from Everglades mangrove peats (∼278 g CO 2 –C m −2 yr −1 ) (Chambers et al., 2014). In our study, vegetation was excluded with the intention of estimating oxidation only from the decomposition of the organic matter present in the soil.…”
Section: Discussionsupporting
confidence: 89%
“…Short-term flooding increases CO 2 concentrations in the soil subsurface upon flooding and increases surface CO 2 flux upon drainage (Jarecke et al, 2016). Other studies in EAA peats with longer flooding periods (14-28 d), such as Hu et al (2017) and Jennewein (2017), found that flood cycles either reduced or did not influence CO 2 emissions compared with drained soils. Our results are similar to Miller et al (2012), who found higher CO 2 efflux in EAA peats exposed to cycles of 1 wk flooded followed by 2 wk drained compared with constantly drained soils.…”
Section: Co 2 Emissionsmentioning
confidence: 92%
See 2 more Smart Citations
“…The rates of denitrification in soils exhibit a high degree of variability because of variation in environmental factors, including soil water content, temperature, bioavailable organic carbon (C), NO 3 ‐ , pH, soil texture and redox potential (Bouwman et al, 2013; Hu, Inglett, Clark, Inglett, & Ramesh Reddy, 2015; Hu, Inglett, Wright, & Reddy, 2016; Hu et al., 2017; Liao, Inglett, & Inglett, 2013; Saggar et al., 2013). These factors interact with each other and hierarchically regulate denitrification rates in soils.…”
Section: Introductionmentioning
confidence: 99%